Analysis of Website User Acceptance through User Testing Model (UTAUT): Case Study of Sidoarjo Dukcapil Plavon Application - Hilman, Muhammad; Pratama, Arista; Safitri, Eristya Maya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the factors influencing the acceptance of the Plavon application in Sidoarjo Regency, utilizing the conceptual model of the Unified Theory of Acceptance and Use of Technology (UTAUT). Through analyzing data from 96 users, the main findings highlight the significant positive influence of performance expectancy, effort expectancy, social factors, and facilitating conditions on users' intention to use the application. Furthermore, facilitating conditions emerge as the primary determinant of user satisfaction. The study underscores the importance of understanding these factors, providing practical guidance for policymakers in budget management, and emphasizing the need to enhance the acceptance and utilization of the Plavon application in the area. Regarding the success of the Plavon application, it was found that performance expectancy, effort expectancy, social factors, and facilitating conditions have a positive and significant impact on users' intention to adopt the application. However, performance expectancy did not exhibit a significant impact in this study's findings.